Empowerment Disaster-Resilient Village Forums for Health Crisis Preparedness: A Participatory Action Research Approach - Sunarto Sunarto; Heru Santoso Wahito Nugroho; Suparji Suparji; Aries Prasetyo; Sulikah Sulikah; Teta Puji Rahayu (Knowledge Dynamics, 2024)
This study aims to enhance the Disaster Resilient Village (Destana) forum's preparedness for disaster-related health crises. The key challenges identified are low community response to early warning systems and slow mobilization of health resources, both contributing to high victim numbers and exacerbating health crises. The study focuses on creating an accessible early warning system and accelerating health resource mobilization, prioritizing these elements based on an analysis of disaster preparedness parameters. Using Action Research with a Participatory Action Research (PAR) design, the research was conducted in Magetan Regency, East Java, involving 150 Destana forum administrators. The study explores the development of early warning procedures, health contingency plans, emergency response structures, and simulation plans. The findings reveal that the Destana forum successfully developed tailored health contingency plans for each village, including an inclusive early warning system Standard Operating Procedure (SOP) for vulnerable groups. Additionally, an integrated health command structure was formed, enhancing emergency response coordination. Emergency response simulations with 90 participants demonstrated improved readiness and community engagement in handling health crises. The study highlights the importance of a participatory, sustainable approach to building resilience, showing that active community involvement fosters collective responsibility for managing health crises during disasters.